CFD and experimental study of slurry erosion wear in Hydro-machinery. (2022) - Sharma, Mithlesh; Kumar Goyal, Deepak; Kaushal, Gagandeep; Kanth Grover, Neel; Bansal, Anuj; Goyal, Khushdeep
Abstract: Hydropower plants which are fed from the tributaries originating from Himalayan ranges face a serious problem due to presence of slurry erosion phenomenon which led to material degradation or failure, sometimes it results in operational failure and economic loss. The main objective of the present work is to show that one can use computational fluid dynamics (CFD) to predict the slurry erosion behaviour and particle impact profiles on hydraulic machinery. To develop the slurry erosion model, Eulerian-Lagrangian based approach is used to simulate the multiphase flow phenomenon i.e. flow behaviour and liquid–solid interaction. For considering the viscosity effect, K-epsilon (k-ε) turbulence model having realizable and scalable wall function is used which simulate the mean flow characteristics for turbulent flow conditions. Furthermore, to track the motion of the particles, the Lagrangian frame of reference was used along with Eulerian formulation for continuous phase. The results obtained from the developed CFD model were in good agreement with the experimentally obtained results.